2011
DOI: 10.3109/0284186x.2011.617388
|View full text |Cite
|
Sign up to set email alerts
|

FOLFOX regimen in pancreatic acinar cell carcinoma: Case report and review of the literature

Abstract: Pancreatic acinar cell carcinoma (PACC) is a rare tumor with a poor prognosis in the absence of surgery. Moreover, there is currently no standard chemotherapy for metastatic PACC.We report the case of a patient treated by the FOlFOX 4 regimen with an objective response and a prolonged tumor control and we provide a review of chemotherapy regimens reported for PACC in the literature. Case reportA 79-year-old man, whose main medical history was a prostatic cancer (2004) treated by hormone therapy and radiotherap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…KRAS , TP53 , CDKN2A (p16), and SMAD4 gene mutations were not typically found in pancreatic ACC , whereas the frequency of mutations in the adenomatous polyposis coli–β catenin pathway, which is rarely detected in PDAC, was similar to those found in colorectal cancer (7%-24%) [17-19]. These findings suggest that the chemotherapeutic approaches for ACC patients include agents known to have activity in colorectal cancer [14,20-22]. …”
Section: Discussionmentioning
confidence: 86%
“…KRAS , TP53 , CDKN2A (p16), and SMAD4 gene mutations were not typically found in pancreatic ACC , whereas the frequency of mutations in the adenomatous polyposis coli–β catenin pathway, which is rarely detected in PDAC, was similar to those found in colorectal cancer (7%-24%) [17-19]. These findings suggest that the chemotherapeutic approaches for ACC patients include agents known to have activity in colorectal cancer [14,20-22]. …”
Section: Discussionmentioning
confidence: 86%
“…This assumption has indeed been supported by isolated case reports and small series. 10,11,13,14 At the current time, however, there have been no clinical trials and there are no established patient selection criteria for the use of the various chemotherapeutic regimens. It is therefore worth directing future efforts toward molecular typing of the tumor and correlating the resulting data with the tumor's response to specific therapeutic agents.…”
Section: Discussionmentioning
confidence: 97%
“…Although no standard chemotherapy for advanced, unrespectable PACC has been established to date, some studies suggested a more favorable efficacy for 5-FU compare with gemcitabine (8). Considering the promising data for FOLFIRINOX against advanced pancreatic cancer (18), the present patient was treated with this regimen.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where curative resection is not applicable due to advanced disease, chemotherapy may be considered. Although no standard therapy for PACC has been established to date due to the rarity of this disease, 5-fluorouracil (5-FU) is considered to be more effective compared with gemcitabine (8). …”
Section: Introductionmentioning
confidence: 99%